2005
DOI: 10.1124/jpet.105.083386
|View full text |Cite
|
Sign up to set email alerts
|

Stilbazulenyl Nitrone, a Second-Generation Azulenyl Nitrone Antioxidant, Confers Enduring Neuroprotection in Experimental Focal Cerebral Ischemia in the Rat: Neurobehavior, Histopathology, and Pharmacokinetics

Abstract: Stilbazulenyl nitrone (STAZN) is a potent lipophilic secondgeneration azulenyl nitrone antioxidant, which is highly neuroprotective in rodent models of cerebral ischemia and trauma. This study was conducted to establish whether the neuroprotection induced by STAZN persists with chronic survival and to characterize STAZNЈs pharmacokinetics. Physiologically regulated rats received a 2-h middle cerebral artery occlusion by intraluminal suture and were treated with either STAZN [four 0.6 mg/kg doses i.p. administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
0
40
1
Order By: Relevance
“…This was not the case prior to MCAo, or at any later survival time (Table 1). Temperature did not affect the extent of tissue salvage achieved with STAZN (0.7 mg/kg) as compared to controls seen in earlier studies (Ginsberg, Becker et al 2003;Ley, Vigdorchik et al 2005). Furthermore, the STAZN dose-response findings in the present study were not confounded by temperature because there were no significant temperature differences between STAZN treatment groups.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…This was not the case prior to MCAo, or at any later survival time (Table 1). Temperature did not affect the extent of tissue salvage achieved with STAZN (0.7 mg/kg) as compared to controls seen in earlier studies (Ginsberg, Becker et al 2003;Ley, Vigdorchik et al 2005). Furthermore, the STAZN dose-response findings in the present study were not confounded by temperature because there were no significant temperature differences between STAZN treatment groups.…”
Section: Discussioncontrasting
confidence: 55%
“…These two sets of results provide important insights into the scope of the neuroprotection conferred by STAZN and support the well-known role of oxygen radicals in contributing to the pathophysiological cascade of molecular events leading to ischemic tissue damage (Schaller, Graf et al 2003). Earlier studies demonstrated that STAZN (0.7 mg/kg, given after 2 hours of ischemia, at the onset of reperfusion) was highly neuroprotective in the MCA suture-occlusion model of transient focal cerebral ischemia (Ginsberg, Becker et al 2003), and that the neuroprotective effect persisted at 30 days (Ley, Vigdorchik et al 2005). The present study confirms our earlier findings for the intermediate dose of STAZN (0.7 mg/ kg).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations